Evaluation of phosphorus fertilizer rate based on Upland Soil Test Kit analysis for tomato fertigation - Alveno, Vitho; D. Susila, Anas; Suketi, Ketty; Maharijaya, Awang (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2024)
Upland Soil Test Kit (PUTK) is a rapid soil analysis kit that estimates the nutrient availability in soil. From previous studies, tomato plant production showed a good correlation with available phosphorus (P) and potassium (K) analysis using the PUTK. This study aimed to find the optimal P fertilizer rate based on PUTK analysis for tomato fertigation. This experiment was carried out using a randomized complete block design, four replications with a single factor, namely P fertilizer rate comprising 0% X, 50% X, 100% X, 150% X, and 200% X, with X the recommended P fertilizer of PUTK on moderate P availability (175 kg ha1). The ANOVA showed that P fertilizer did not significantly affect the vegetative growth, production, and fruit quality of tomatoes. It means that PUTK analysis had low accuracy as a basis for determining the optimum P fertilizer rate for tomato fertigation. The low accuracy could be due to PUTK underestimating the status of soil P availability. Mechlich-1 analysis showed that the experimental field had high P availability (44.6 ppm), while PUTK analysis still indicates moderate P availability. This shows that PUTK needs to be developed further, especially quantifying the result to help make informed and accurate decisions. Keywords: precision farming; precision fertilization; Upland Soil Test Kit; FERADS; sustainable agriculture